Sampling and testing for quality assurance of pavement preservation and treatments - Sebaaly, Peter (Revista Ingeniería de Construcción, 2024)
Pavement preservation is essential to maintaining viable road infrastructure, slurry seal and microsurfacing, referred to as “slurry system” are widely used as cost-effective techniques for preserving asphalt concrete pavements. However, there is a need for better quality assurance (QA) tools to ensure compliance with approved job mix formulas. This research aimed to devise a field sampling procedure for slurry systems and develop a reliable and accurate QA system to determine the water content and asphalt residue content present in slurry mixes. To be deemed adequate, sampling techniques must satisfy three main criteria: sufficient amount of sampled mixture to determine asphalt residue content, safety of the sampler, and uniform and consistent collected samples. The utility cover sampling technique involves placing a non-absorptive material over a utility cover, as the mix spreader applies the mixture, the cover gets coated with a layer of slurry. This study found that asphalt felt was the most successful material for slurry mix sample collection from utility covers. The study concluded that the oven evaporation method is effective in determining the water content and the ignition oven test is effective in determining the asphalt residue content in slurry mixes.